Engineered wood i-joist from jointed oriented strand board (OSB) web and solid wood flanges / Wan Mohd Nazri Wan Abdul Rahman, Suhaimi Muhammed and Abdul Jalil Ahmad - Wan Abdul Rahman, Wan Mohd Nazri; Muhammed, Suhaimi; Ahmad, Abdul Jalil (2001)
Problems of low-cost housing system have continued to be a primary research and development area for the engineering use of wood composite such as plywood and oriented strand board (OSB). As composites, their properties should be developed to suit their erid use and they are now able to replace solid wood in many situations. For example, this study proved that there is a good potential for the manufacture and application of prefabricated wood I-joist. I-joist is a modern wood product that can be used as a housing construction material such as roof and floor systems. I-joist is a system that consists of flanges and web components, both have to work together as a system in order to match the strength property of solid wood beam.